Gorky's Tolstoy & other reminiscences : key writings by and about Maxim Gorky - Gorky, Maksim, 1868-1936 (Russian literature and thought series., 2008)
Maxim Gorky (1868-1936) enjoyed worldwide fame of a kind unmatched by that of any other writer in the first half of the twentieth century. Prodigiously gifted and prolific, riddled with contradictions, praised increasingly for political rather than literary reasons, he left a vast body of writing that contains acknowledged masterpieces alongside many currently neglected works that still await impartial assessment.Taken together, the pieces in this book (many of them based on fuller texts than those of previously published translations) present a surprising and unfamiliar Gorky--a figure who, once the clichés are stripped away from him, becomes ever more fascinating and enigmatic as man, as writer, and as historical figure. Among the volume's selections are portraits of Gorky by four particularly astute observers: poet Vladislav Khodasevich, critics Boris Eikhenbaum and Georgy Adamovich, and novelist Evgeny Zamiatin.Fanger's generous annotations and brilliant introduction will make this book indispensable to every reader with an interest in Tolstoy, Gorky, modern Russian literature and politics, or the art of the memoir.